A Comparison of Clinical Characteristics and Outcomes of Ventilator-Associated Pneumonias Among Burn Patients by Diagnostic Criteria Set. Issue 6 (December 2017) - Younan, Duraid; Griffin, Russell; Swain, Thomas; Schinnerer, Eric; Pittet, Jean-Francois; Camins, Bernard
ABSTRACT: Objectives: The National Healthcare Safety Network (NHSN) replaced its old definition for ventilator-associated pneumonia (VAP) with ventilator-associated events (VAEs) in 2013. Little data is available comparing the two definitions in burn patients. Methods: Data from 2011 to 2014 were collected on burn patients mechanically ventilated for at least 2 days. VAP was determined using two methods: (1) pneumonia as defined by the previous more clinical CDC (NHSN) definition captured in the burn registry; (2) pneumonia as defined by the recent CDC (NHSN) standard of VAEs where patients meeting the criteria for possible VAP were considered having a pneumonia. Cohen kappa statistic was measured to compare both definitions, and chi-square and ANOVA to compare admission and clinical outcomes. Results: There were 266 burn patients who were mechanically ventilated for at least 2 days between 2011 and 2014. One hundred patients (37.5%) met the criteria by the old definition and 35 (13.1%) met the criteria for both. The kappa statistic was 0.34 (95% confidence interval 0.23–0.45), suggesting weak agreement. Those who met both definitions were mechanically ventilated for a longer period of time ( P  = 0.0003), and had a longer intensive care unit (ICU) length of stay (LOS) ( P  = 0.0004) and hospital LOS ( P  = 0.0014). Conclusions: There is weak agreement between the two definitions of VAP in severely burn patients. However, patients who met both VAP definitions had longer ventilator days, ICU, and hospital stays.